The effect of pump laser pulse chirp on the properties of generated nonlinear Thomson scattering radiation - Wang, Zi; Xu, Junyuan; Li, Jiachen; Zheng, Qianmin; Tian, Youwei (Frontiers in Physics, 2025)
In order to explore better electron radiation properties, we introduce laser pulses with different chirps and different pulse widths to drive electrons to produce relativistic nonlinear Thomson scattering. We numerically simulate electron radiation.The relativistic electron dynamics and resulting Thomson scattering spectra are calculated using a nonlinear model, incorporating the electronic response function under chirped conditions. We found that under the influence of chirp, the laser pulse width produces a regular change in the radiation properties of excited electrons. The peak radiation pulse increases and then decreases with increasing pulse width, while the FWHM decreases with increasing pulse width, Almost 103 orders of magnitude larger in chirped condition than in no-chirp condition, and the radiation characteristics of negative chirp are Almost an order of magnitude less than positive chirp for the same pulse width and the same absolute value of chirp parameter. In addition, we verify that the electronic response function still holds under chirp conditions, and we are surprised to find that the electronic response function can also be used to measure the gain of chirp on the radiated power, which provides a brand new perspective for the deep understanding of the role of chirp. This work suggests potential applications in high-field physics and compact radiation source design, where chirp engineering could enhance performance.